Preeclampsia history and postpartum risk of cerebrovascular disease and cognitive impairment: Potential mechanisms - Beckett, Ashtin G.; McFadden, Mia D.; Warrington, Junie P. (Frontiers in Physiology, 2023)
Hypertensive disorders of pregnancy such as preeclampsia, eclampsia, superimposed preeclampsia, and gestational hypertension are major causes of fetal and maternal morbidity and mortality. Women with a history of hypertensive pregnancy disorders have increased risk of stroke and cognitive impairments later in life. Moreover, women with a history of preeclampsia have increased risk of mortality from diseases including stroke, Alzheimer’s disease, and cardiovascular disease. The underlying pathophysiological mechanisms are currently not fully known. Here, we present clinical, epidemiological, and preclinical studies focused on evaluating the long-term cerebrovascular and cognitive dysfunction that affect women with a history of hypertensive pregnancy disorders and discuss potential underlying pathophysiological mechanisms.